How free trade agreement affects the success of China's Belt and Road infrastructure projects - Beibei Hu; Yuying Jin; Kai Wang (International Studies of Economics)
Abstract After China launched the Belt and Road Initiative in 2013, the Chinese government has invested over 1200 infrastructure projects in countries along the Belt and Road, and nearly 10% of the projects have failed or been delayed. China has also concluded free trade agreements with many countries along the Belt and Road to reduce trade and investment barriers to promote economic and trade cooperation. This paper analyzes whether the signing of the free trade agreement (FTA) is conducive to promoting China's infrastructure investment projects’ success in the countries along the Belt and Road. We conclude that the signing of the FTA agreement is conducive to reducing the failure rate of China's infrastructure investment in the countries along the Belt and Road. For deeper FTAs, the effect is more pronounced. This paper further explores the investment provision of FTA and concludes that investment provision can improve the success rate of investment, especially if it includes provision of national treatment in the pre‐establishment and the dispute settlement mechanism.